Dual kidney transplantation offers a safe and effective way to use kidneys from deceased donors older than 70 years - Lee, Kyo Won (BMC Nephrol, 2020)
PURPOSE: Dual kidney transplantation (DKT) offers a way to extend the use of kidneys from expanded criteria donors (ECDs). Here, we compared the outcomes of DKT with those of single kidney transplantation from standard criteria donors (SCDs) and ECDs. METHODS: In 2014, we began performing DKT using both kidneys from deceased donors greater than 70 years of age with one of two risk factors: serum creatinine (sCr) level over 3.0 mg/dl or eGFR under 30 ml/min. By 2017, we had performed 15 DKTs. We compared the outcomes of the 15 DKT recipients with those of 124 patients who received a kidney from an SCD and 80 patients who received a kidney from an ECD. RESULTS: Compared with ECDs and SCDs, DKT donors were older, had a higher diabetes burden, and a higher sCr level (p < 0.01, < 0.01, and 0.03, respectively). DKT recipients were also older and had a higher diabetes burden than recipients of kidneys from ECDs and SCDs (p < 0.01, both). DKT recipients had a lower nadir sCr and shorter duration to nadir sCr than single ECD KT recipients (p < 0.01and 0.04, respectively). CONCLUSIONS: The survival rates of DKT grafts were compatible with those of single KT grafts. Therefore, DKT may be considered a suitable an option to expand the donor pool.